2023
DOI: 10.14336/ad.2022.0916
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism in Central Nervous System Diseases: Pathophysiology and Potential Therapeutic Strategies

Abstract: The metabolism of L-tryptophan (TRP) regulates homeostasis, immunity, and neuronal function. Altered TRP metabolism has been implicated in the pathophysiology of various diseases of the central nervous system. TRP is metabolized through two main pathways, the kynurenine pathway and the methoxyindole pathway. First, TRP is metabolized to kynurenine, then kynurenic acid, quinolinic acid, anthranilic acid, 3-hydroxykynurenine, and finally 3-hydroxyanthranilic acid along the kynurenine pathway. Second, TRP is meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 199 publications
1
11
0
Order By: Relevance
“…Notably, IDO increases were significantly enhanced in parallel to increased levels of IFN-γ, IL-1β, and TNF-α, in both WT and Tg2576 mice, further suggesting that IDO activity likely follows innate immune responses to VEEV TC-83 infection and serves as the initiation step of TRP metabolism in the CNS [43]. This aligns with the notion that inflammatory conditions, despite their generation, stimulate TRP degradation and are related to increased levels of KP metabolites in the brain [23], including the neuroprotective KYNA and neurotoxic QUIN [44]. This is further supported by clinical studies identifying heightened IDO activity, increased KYN/TRP ratios, and increase concentrations of TNF-α, IL-6, IFN-γ, CCL2, and CXCL10 in CHIKV patients [42].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Notably, IDO increases were significantly enhanced in parallel to increased levels of IFN-γ, IL-1β, and TNF-α, in both WT and Tg2576 mice, further suggesting that IDO activity likely follows innate immune responses to VEEV TC-83 infection and serves as the initiation step of TRP metabolism in the CNS [43]. This aligns with the notion that inflammatory conditions, despite their generation, stimulate TRP degradation and are related to increased levels of KP metabolites in the brain [23], including the neuroprotective KYNA and neurotoxic QUIN [44]. This is further supported by clinical studies identifying heightened IDO activity, increased KYN/TRP ratios, and increase concentrations of TNF-α, IL-6, IFN-γ, CCL2, and CXCL10 in CHIKV patients [42].…”
Section: Discussionsupporting
confidence: 66%
“…Several viral infections, including HIV [19], HCV [20], and HSV [21] increase activation of the KP, which interestingly is implicated in the neurological and cognitive impairments of patients with HIV, HCV, and HSV [21,22]. Moreover, inflammation induces the activation of indoleamine 2,3-dioxygenase (IDO) and diverts TRP metabolism from serotonin to KYN, reducing the availability of CNS-localized serotonin [23]. Triggering KYN levels results in the increased activation of several enzymes and generation of neuroprotective and neurotoxic metabolites including kynurenic acid (KYNA), 3-hydroxykynurenine (3-HK), and quinolinic acid (QUIN), ultimately leading to the generation of NAD+ [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions in the KYN pathway and alterations in Trp metabolism have been linked to increased intestinal permeability and immune dysregulation. These disturbances contribute to the development and progression of various GI disorders, including IBD, CRC, cardiovascular diseases, nervous system disorders, infectious diseases, and hepatic fibrosis [78,80,[87][88][89][90][91][92]. The influence of these metabolites on the pathogenesis of these conditions underscores their significant role in GI health and highlights the importance of maintaining proper KYN pathway function and Trp metabolism.…”
Section: Trpmentioning
confidence: 99%
“…For example, it has been shown that KYNA and its synthetic analogs, such as SZR-72 and SZR-104, possess the ability not only to influence motor domains of behavior but also to potentially modulate emotional responses [87]. Therefore, KYNA appears to be a potential drug candidate for the treatment of neuropsychiatric disorders because it can regulate the balance between neurotoxicity and neuroprotection [70,[88][89][90][91][92][93][94][95][96]. However, more research is needed to evaluate its safety and efficacy an its interactions with other metabolic pathways of Trp.…”
Section: Introductionmentioning
confidence: 99%